Seroprevalence of hemorrhagic septicemia in dairy cows in Assam, India - Shome, R.; Deka, Ram Pratim; Sahay, S.; Grace, Delia; Lindahl, Johanna F. (Informa UK Limited, 2019)
Hemorrhagic septicemia (HS) is a highly fatal disease caused by Pasteurella multocida that often cause outbreaks in buffalo and cattle in India, and thus is a major cause of production losses. It is one of the livestock diseases with the highest mortality, and despite available vaccines, outbreaks still occur. To assess the seroprevalence in the state of Assam, Northeast India, 346 serum samples from cows from 224 randomly selected households, from both urban and rural areas of three districts, were tested with a commercial ELISA. In total 88 cows were seropositive (25.4%), and indigenous cattle were significantly more seropositive (33.5%) compared to the crossbred cattle (18.5%) (p = 0.002). Herd prevalence was 35.7%, and more rural farms (47.4%) were positive compared to the urban farms (23.6%) (p < 0.001). No other risk factors were identified in this study. Only one farm had vaccinated against HS, but there were no seropositive animals detected in that herd. This study shows that HS is highly prevalent in Assam. Considering the importance of dairy production in India, and the dependence of the rural Assam population on farming and livestock keeping, more extensive vaccination campaigns would be important.